2015
DOI: 10.1007/s00270-015-1107-2
|View full text |Cite
|
Sign up to set email alerts
|

Curved Needles in CT-Guided Fine Needle Biopsies of Abdominal and Retroperitoneal Small Lesions

Abstract: Using curved needles, there is an effective improvement in CT-guided FNA of abdominal and retroperitoneal small lesions which are difficult to achieve with conventional CT or ultrasound guide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Seven out of 8 (87.5%) trajectories were out of plane (≥ 5° in the z -axis), thus countering one of the CT limitations in guiding needle insertion when outside the axial plane identified by Wood et al [ 12 ]. Indeed, visualisation of the full length of needles outside the axial plane is difficult on CT imaging as several axial planes must be reviewed to visualise the full length of the needle, or volume with multiplanar reconstruction must be performed thus losing the nearly real-time ability of the CT and increasing irradiation [ 13 ]. Slight angulation can be managed with an associated gantry angulation when possible.…”
Section: Discussionmentioning
confidence: 99%
“…Seven out of 8 (87.5%) trajectories were out of plane (≥ 5° in the z -axis), thus countering one of the CT limitations in guiding needle insertion when outside the axial plane identified by Wood et al [ 12 ]. Indeed, visualisation of the full length of needles outside the axial plane is difficult on CT imaging as several axial planes must be reviewed to visualise the full length of the needle, or volume with multiplanar reconstruction must be performed thus losing the nearly real-time ability of the CT and increasing irradiation [ 13 ]. Slight angulation can be managed with an associated gantry angulation when possible.…”
Section: Discussionmentioning
confidence: 99%
“…3). 28,29 The first step of this technique involves advancement of a 13-to 18-gauge guide needle close to the intended target. The tip of a 22-gauge needle (Chiba, Cook Medical, Bloomington, IN) is then gently curved with hemostat forceps based on the curvature needed to bridge the gap between the guide needle tip and the target.…”
Section: Curved Needle Tipmentioning
confidence: 99%
“…De Filippo et al found that the curved needle technique facilitated cytological diagnosis in 25 of 25 cases with no complications. 29 A novel, commercially available, steerable needle is also available (Morrison; AprioMed AB, Uppsala, Sweden). This device is a 21-gauge, 17-cm-long needle with a Menghini double bevel tip.…”
Section: Curved Needle Tipmentioning
confidence: 99%
“…In order to avoid these complications and obtain pathological con rmation, more and more oncologists adopt and approve percutaneous image-guided biopsy technique that is routinely used for differential diagnosis, clinical staging, biological analysis and therapeutic strategy. Although CT-guided biopsy has high spatial resolution and visibility to achieve relatively satisfactory samples, the presence of nonportability, ionizing radiation, and high operating cost and time obviously hinder its clinical application (10,11). Interestingly, US-FNAC is obtaining a important impact owing to real-time precise visualization and tracking, especially when there are vital structures adjacent to target lesion, including abdominal aorta, inferior vena cava, and gastrointestinal tract (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%